The upshot of generation mix variation in electricity tariff via system dynamics approach: Malaysia circumstances / Norlee Husnafeza Ahmad, Nofri Yenita Dahlan and Nor Erne Nazira Bazin - Ahmad, Norlee Husnafeza; Dahlan, Nofri Yenita; Bazin, Nor Erne Nazira (Universiti Teknologi MARA, 2021)
Generation mix for electricity literally denotes the mix of various energy used in order to generate electricity. No matter what type of market model one country is using, generation mix is the key in power generation especially when tariff and sustainability are the main concerns. At present, the generation mix is undergoing significant changes in the world. In Malaysia, generation mix mostly is dominated by oil during early years up until the 5th Fuel Diversification Policy is introduced. From 85% of electricity generation of oil in early 1980s, it drops until 5% after the policy is established. Globally, the generation mix is continuously varying and the electricity market equilibrium analysis in this new circumstances is essential to the market regulator, operator, and partner. Therefore, this paper thoroughly investigate the impact of generation mix variation on electricity tariff in Malaysia by using System Dynamics as the approach for a 30 years span of time. A System Dynamics model is developed in order to look at the rapport between generation mix and electricity tariff. The result validates the significant effects on electricity tariff with the variation of generation mix.